Synthesis and Spectral Studies of Schiff Base Receptor for Fluorescence Detection of Hg(II) - Anbuselvan, Chinnadurai (Asian Journal of Chemistry, 2019)
In this study, a fluorescent film probe with a structure centered on a Schiff base viz. (N1′,N2′)-N1,N2-bis(2-amino-3,5-dibromobenzylidene)-1,2-diamine (DAB) was synthesized. The probe was used as a fluorescence chemosensor for transition metal ion detection in an aqueous medium. Fluorescence was measured through fluorescence spectroscopy, and the emission maximum of the proposed sensor was 552 nm. Furthermore, the proposed film sensor exhibited a high sensitivity and selectivity toward Hg2+ ions. The limit of detection (LOD) of chemosensor, which was calculated using the fluorescence titration method, found to be 2.11 μM at 552 nm. The fluorescence spectroscopic data evidenced the potential of the proposed sensor for application in the detection and determination of Hg2+ ions in deionized water without the interference from other metal ions.